OBSTRUCTIVE SLEEP APNEA AND ITS IMPACT ON ATHLETES AND SPORTS PERFORMANCE – THE REVIEW - Kinga Wiechnik; Joanna Wrona; Aleksandra Kaźmierczyk; Jędrzej Kęsik; Daria Madycka; Kacper Michta; Małgorzata Słaboń; Karol Stępniak; Wiktor Telega; Aleksandra Wójcik (International Journal of Innovative Technologies in Social Science, 2025)
Obstructive sleep apnea (OSA) is a prevalent and underdiagnosed condition with significant systemic health implications. It is characterized by recurrent upper airway collapse during sleep, leading to intermittent hypoxia, sleep fragmentation, and an array of comorbidities. Among the risk factors, obesity is the most common, but other factors such as sex, age, tonsillar hypertrophy, and the presence of comorbid conditions also play a role. Untreated obstructive sleep apnea (OSA) can lead to cardiovascular diseases, diabetes, strokes, and even sudden death. Diagnosis is based on medical history, clinical examination, and most importantly, polysomnographic testing. Treatment includes lifestyle modifications, continuous positive airway pressure (CPAP) therapy, and in some cases, surgical interventions. This literature review synthesizes current evidence regarding the pathophysiology, clinical presentation, diagnostic approaches, and therapeutic options for OSA in adults.